Electrochromic performance of sol–gel derived amorphous MnO2–ZnO nanogranular composite thin films - Falahatgar, S.S.; Ghodsi, F.E.; Tepehan, F.Z.; Tepehan, G.G.; Turhan, İ.; Pishdadian, S. (Elsevier BV, 2015)
Abstract In this work, the MnO2–ZnO thin films with nominal molar ratios of 8%, 16% and 25% of Zn to Mn were deposited on glass and Indium Tin Oxide (ITO) substrates by dip-coating sol–gel method and annealed in air at 300 °C. The films were characterized by Cyclic Voltammetry measurement (CV), X-ray Diffraction spectroscopy (XRD), Atomic Force Microscopy (AFM), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray spectroscopy (EDX) and UV–Visible spectrophotometry. The XRD patterns indicated the amorphous structure for all samples. The CV measurements were performed in the potential window between − 2 V and 2 V at a potential scan rate of 20 mV/s and 50 mV/s. The results of CVs at a scan rate of 20 mV/s in the first cycle showed that the sample with 25% of Zn content with the maximum anodic and cathodic charge density has a better performance compared to other samples and the capacitance decreases with increasing cycle number of all samples at 50 mV/s. Optical constants and optical band gaps of thin films were investigated by transmission and reflection. The AFM images revealed that roughness increases with increasing Zn concentration. The FE-SEM images showed nearly similar morphology for all thin films.